A historical typhoon database for the southern and eastern Chinese coastal regions, 1951 to 2012. (May 2015) - Yap, Wenshu; Lee, Yingsin; Gouramanis, Chris; Switzer, Adam D.; Yu, Fengling; Lau, An Yi Annie; Terry, James P.
Abstract: Historically, typhoons have inflicted significant damage and loss of life to coastal communities in Asia. Regional governments, private enterprise (including the insurance and re-insurance industries), town planners and coastal developers are grappling to find sustainable solutions to coastal development while maintaining high rates of development and economic growth. Several nations and organisations have developed typhoon databases to collate the impacts of typhoons in various regions. However, these databases are not comparable or consistent in terms of the depth of information provided. This paper presents a new typhoon database for southern and eastern Chinese coastal regions (SECCR) spanning the period from 1951 to 2012. The database comprises comprehensive details of typhoons impacting Hong Kong, Taiwan, and the mainland Chinese provinces of Hainan, Fujian, Guangdong and Zhejiang. This new database provides an insight into the impacts of typhoons upon the economies and casualties suffered in each of the SECCR. There were 853 typhoons between 1951 and 2012, 286 typhoons caused human casualties, and 228 inflicted economic loss. The data shows an overall decrease of fatalities and economic loss. The database also shows a downward trend in the percentage of normalized economic loss in relation to the regional annual gross domestic product (GDP) for each province. The decline in both fatalities and relative economic losses in the SECCR may reflect improved adaptation and mitigation strategies to the impacts of typhoons in the Chinese coastal region. Further examination into the spatial and temporal features of typhoons that bring catastrophic damage to the SECCR can be managed with this newly developed database. This database can also act as a guide for future direction in improving mitigation strategies of the region. Highlights: A database of the physical characteristics of typhoons affecting southern China. First linkage of a typhoon database to socio-economic indicators in the region. Examination of the links between typhoons and socio-economic factors from 1951 to 2012.